Pengawasan Otoritas Jasa Keuangan terhadap Pelaku Usaha Pegadaian Illegal - Budiarto Sembiring; Isnaini Isnaini; Jelly Leviza (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This paper aims to examine and analyze the legal rules regarding pawnshops, OJK supervision of illegal pawnshop business actors at OJK Regional Office 5 North Sumatra and the obstacles faced in OJK supervision of illegal pawnshop business actors at OJK Regional Office 5 North Sumatra. To approach this problem, the theory of the legal system is used. The data were collected through interview guidelines and analyzed qualitatively. This study concludes that the legal rules regarding pawnshops are regulated in Law Number 40 of 2007 concerning Limited Liability Companies, Law Number 17 of 2012 concerning Cooperatives, Financial Services Authority Regulation Number 31/POJK.05/2016 concerning OJK's Pawnshop Business. OJK's supervision of illegal business actors in OJK Region 5 North Sumatra has not been carried out strictly, it even seems that the OJK has neglected it. The obstacles faced in OJK's supervision of illegal business actors are: there is no legal regulation regarding sanctions that can be given to illegal pawnshop business actors, many pawn business actors cannot meet the capital requirements set by OJK, OJK's cooperation with SWI is still weak because there is an assumption that the problem of illegal pawn business actors is not too urgent to be taken care of so that it seems to be ignored, the public's lack of concern so that they continue to use illegal pawnshop business services, as well as less intensive socialization about pawn business licensing.